2009
DOI: 10.1080/02640410902887283
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social variables and moral disengagement on prosocial and antisocial behaviours in field hockey and netball

Abstract: In this study, we examined: (a) the effects of perceived motivational climate and coaching character-building competency on prosocial and antisocial behaviours towards team-mates and opponents in field hockey and netball; (b) whether the effects of perceived character-building competency on sport behaviours are mediated by moral disengagement; and (c) whether these relationships are invariant across sport. Field hockey (n = 200) and netball (n = 179) players completed questionnaires assessing the aforementione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
94
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 30 publications
14
94
0
6
Order By: Relevance
“…Soccer players who reported higher aggression and peer cheating tended to evaluate their coach higher in understanding competitive game strategy. Previous studies examining athletes' perceptions of their coach's competency and effectiveness have found that the character‐building dimension was associated with their prosocial and antisocial behaviors (Boardley & Kavussanu, ; Boardley et al., ). However, these studies did not examine the game strategy dimension in primary analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Soccer players who reported higher aggression and peer cheating tended to evaluate their coach higher in understanding competitive game strategy. Previous studies examining athletes' perceptions of their coach's competency and effectiveness have found that the character‐building dimension was associated with their prosocial and antisocial behaviors (Boardley & Kavussanu, ; Boardley et al., ). However, these studies did not examine the game strategy dimension in primary analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The study used validated measures of relational support and on and off-field antisocial and prosocial behaviour (using a different, but related measure to the prosocial measure used in the Football United study) and found prosocial behaviour was influenced by relational support provided by the coach and the team attitude towards fair play [46]. Other studies support the role of coaches in promoting pro-scoial behaviour [42]. In our study, we cannot specifically point to the role of coaches as the main factor in our findings on prosocial behaviour, though many interviewees commented on the satisfying experience they had as coaches and of being coached.…”
Section: Discussionmentioning
confidence: 99%
“…The overall qualitative data set was first analysed inductively and thematically with constant comparison undertaken, that is, comparison of the views of interview participants within and between schools [31]. NVIVO 9, a qualitative data management tool, was used by the main field researcher [42] and all data coded to nodes created iteratively with movement between the data set and nodes. Discussion between the field researcher and lead investigator was ongoing throughout the initial coding and this assisted in the refinement of nodes and identification of key themes.…”
Section: Methodsmentioning
confidence: 99%
“…Seria então um desligamento da moral, um conjunto de processos subjacentes à regulação da conduta moral, o que implica na negação da culpa diante da reprovação que suas condutas provocam nas outras pessoas (Bandura, 1991). Bandura (1991) estimulou estudos sobre o desengajamento moral, o qual foi pesquisado em vários contextos sociais, como o terrorismo (Maikovich, 2005), a perpetração de desumanidades (Bandura, 1999), as mortes em games controladas por jogadores (Royakkers & van Est, 2010), a função dos carrascos (Osofsky, Bandura, & Zimbardo, 2005), o bullying na escola (Menesini et al, 2003;Obermann, 2011), em estudantes de escolas de negócios (Cory, 2015), no esporte (Boardley & Kavussanu, 2009;Shields, Christopher, & Bredemeier, 2015;Tsai, Wang, & Lo, 2014), em imigrantes refugiados requerentes de asilo (Greenhalgh, Watt, & Schutte, 2015), em prisões (South & Wood, 2006), em empreendedores (Baron, Zhao, & Miao, 2015), entre outros. Além dos estudos com a participação de Bandura, o contexto corporativo gerou interesse na aplicação da teoria do autor (Bandura, 1991) Comportamento ético e comportamento moral são diferentes.…”
Section: Quando a Conduta Corporativa Torna-se Um Crime Corporativo: unclassified